2018 Integrated Communications, Navigation, Surveillance Conference (ICNS) 2018
DOI: 10.1109/icnsurv.2018.8384838
|View full text |Cite
|
Sign up to set email alerts
|

ADS-B mixed SUAS and NAS system capacity analysis and DAA performance

Abstract: Automatic Dependent Surveillance-Broadcast (ADS-B) technology was introduced more than twenty years ago to improve surveillance within the US National Airspace Space (NAS) as well as in many other countries.Via the NextGen initiative, implementation of ADS-B technology across the US is planned in stages between 2012 and 2025. ADS-B's automatic one second epoch packet transmission exploits on-board GPS-derived navigational information to provide position information, as well as other information including vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…These are mainly connected with the future intended operation in VLL, without transported persons on board. According to the statement of ICAO [17,18], the widespread provision of UA ADS-B (Out) in mode S on the frequency band 1090 MHz (1090 ES) is inappropriate due to the already considerable congestion of this band, which is at the limit of its capacity. Another obstacle can be the height of the UAS operation, and therefore the risk of signal reflection from physical obstacles (buildings) and the resulting interference.…”
Section: Technologymentioning
confidence: 99%
“…These are mainly connected with the future intended operation in VLL, without transported persons on board. According to the statement of ICAO [17,18], the widespread provision of UA ADS-B (Out) in mode S on the frequency band 1090 MHz (1090 ES) is inappropriate due to the already considerable congestion of this band, which is at the limit of its capacity. Another obstacle can be the height of the UAS operation, and therefore the risk of signal reflection from physical obstacles (buildings) and the resulting interference.…”
Section: Technologymentioning
confidence: 99%
“…In [21], a similar scenario was studied, also considering the current regulatory practices of the U.S. National Airspace System, and the authors finally reported that ADS-B should be used along with some other system, especially optical sensors for collision avoidance. Other works were focused on the simulation of the ADS-B mounted on UAS to evaluate performance at low altitudes [22] or to propose collision-avoidance algorithms based on the ADS-B information [23].…”
Section: Ads-bmentioning
confidence: 99%
“…Previous studies by MITRE and NASA determined that 1,400 or more ADS-B-equipped small, unmanned aircraft can be supported below 400 ft in a metropolitan area without frequency saturation if they use a low power setting (17,18). Although passenger carrying UAM operations will operate above 400 ft, the tradeoff between flight speed, aircraft density, and power setting provides flexibility to manage ADS-B frequency saturation and is not anticipated to restrict UAM operations.…”
Section: Communication Navigation and Surveillancementioning
confidence: 99%